2011
DOI: 10.1002/app.34042
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical behavior of unsaturated polyester [derived from poly(ethylene terephthalate) waste] and montmorillonite‐filled nanocomposites synthesized by in situ polymerization

Abstract: Postconsumer poly(ethylene terephthalate) waste bottles were glycolyzed as precursors of unsaturated polyester resin (UPR) and their montmorillonite (MMT)-filled nanocomposites. The glycolysis product (hydroxyl-terminated oligomers) was converted into UPR with various acid contents. These resins were miscible with styrene and could be cured with peroxide initiators to produce thermosetting unsaturated polyester (UP). Nanocomposites composed of UP matrix and organically modified clay were prepared by in situ po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Katoch and Kundu carried out the production of unsaturated polyester based on MMT nanocomposites by in situ polymerization. Poly(ethylene terephthalate) waste bottles were glycolyzed as precursors of polyester matrix.…”
Section: Nanocomposite Preparationmentioning
confidence: 99%
“…Katoch and Kundu carried out the production of unsaturated polyester based on MMT nanocomposites by in situ polymerization. Poly(ethylene terephthalate) waste bottles were glycolyzed as precursors of polyester matrix.…”
Section: Nanocomposite Preparationmentioning
confidence: 99%
“…By using this in situ polymerization technique, exfoliated PET nanocomposites were produced with significant reductions in oxygen gas permeability. Katoch and Kundu29 have also reported the production of unsaturated polyester‐styrene based nanocomposites through an in situ type polymerization. By introducing the organoclay simultaneously with the monomers, nanocomposites with mixed intercalated/exfoliated morphologies were produced.…”
Section: Introductionmentioning
confidence: 99%
“…Katoch and Kundu 15 reported that T5 and T10 are generally used to evaluate the thermal stability of the bulk polymer, whereas T50 reflects the consistency of the cross-linked networks of the bulk polymer. It is evident that UP and all nanocomposite samples display one main step degradation between 400°C and 500°C, which can be attributed to the chain scission of polystyrene and polyester fragments.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…In the field of polymer-based nanocomposites, a wide variety of materials are used as fillers, but much concern has been focused on layered silicates. [15][16][17][18][19][20] Among various thermoset resins, UPs are the most widely used matrix materials in polymeric composites. The major advantages of UP resins are a balance of mechanical, chemical, thermal, and electrical properties; low cost; and ease of handling and processing.…”
Section: Introductionmentioning
confidence: 99%